2009
DOI: 10.1007/s00467-009-1215-9
|View full text |Cite
|
Sign up to set email alerts
|

Growth failure associated with sirolimus: case report

Abstract: An 11-year-old girl, who was a renal transplant recipient, developed linear growth failure associated in time with sirolimus (SRL) treatment. After 5 years of functional graft [creatinine clearance (CCr) 90 ml/min per 1.73 m(2) body surface area], she developed acute renal failure due to calcineurin inhibitor-related hemolytic uremic syndrome, and cyclosporine A was replaced by SRL. Before the drug change, she had been growing normally (5.5 cm/year) and had reached the 33.9 percentile (P) of height (z-height -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 16 publications
2
16
1
Order By: Relevance
“…The antiproliferative effects of everolimus did not seem to negatively influence patient growth in this study, although growth inhibition has been reported for a patient receiving sirolimus (23). Even with late steroid elimination at 9-month post-KTX, and the inclusion of patients without further growth potential because of age, the growth of patients during this 3-year observation period was slightly greater than the growth of patients reported in other trials (2,7).…”
Section: Discussioncontrasting
confidence: 67%
“…The antiproliferative effects of everolimus did not seem to negatively influence patient growth in this study, although growth inhibition has been reported for a patient receiving sirolimus (23). Even with late steroid elimination at 9-month post-KTX, and the inclusion of patients without further growth potential because of age, the growth of patients during this 3-year observation period was slightly greater than the growth of patients reported in other trials (2,7).…”
Section: Discussioncontrasting
confidence: 67%
“…(25) and decreased endochondral bone growth (26). A girl was described that stopped growing after switch from CsA to Sirolimus in one case report (27). Even with late steroid elimination 9 months after KTX, growth in the first year after kidney KTX (growth velocity 4.5 ± 4.4 cm/year) was comparable with other trials (2,7).…”
Section: We Recognized Problems With Wound Healing In Two Children Wsupporting
confidence: 54%
“…Except for gender and primary renal disease, the results are expressed as mean ± SD association of those three conditions facilitates the occurrence of catch-up growth in pediatric kidney transplant on immunosuppressive treatment with CNIs and mycophenolate [20][21][22][23][24][25][26][27]. In agreement with this assumption, our control group of patients with a mean age at the study entry of 4.7 years, mean corticosteroid dose during follow-up of approximately 2 mg/day and normal GFR exhibited a positive change in the height Z score whereas this effect was not found in the subgroup of SRL-treated patients with similar age, prednisone dose and renal function ( It is of note that preliminary experimental data [28] and a single case report [15] indicate that treatment with recombinant human growth hormone (rhGH) may reverse, at least partially, the negative effect on longitudinal growth caused by SRL. However, as occurred in our study and in other studies [9][10][11], the development of a malignant tumor was one of the main causes for replacing CNIs by SRL in transplanted children, which may represent a contraindication to prescribe rhGH therapy in those patients.…”
Section: Discussionmentioning
confidence: 83%
“…This hypothesis has not been assessed in pediatric clinic trials and only a single case report analyzes growth and the response to growth hormone therapy in a child treated with SRL [15].…”
Section: Introductionmentioning
confidence: 96%